A importância da preservação do patrimônio imaterial nas esferas educacionais e culturais de São Pedro do Sul: práticas do saber natural no meio rural - Bidel, Eloiza Helena de Carvalho (2024)
The preservation of intangible heritage emerges from the need to historically contribute to valuing the identity of a people. Through this, throughout the research, we sought to understand the importance of heritage in its different spheres as an instrument for recognizing history. With regard to popular wisdom, the research aimed to give a voice and opportunity to speak to women in rural areas of the city of São Pedro do Sul and through this, material was created aimed at raising awareness about the need to preserve to remember. Through ancestral knowledge passed down from generation to generation by women who were formerly witches burned at the stake, you can recognize in local culture the history of medicinal herbs used as a healing tool for different diseases. So that all the historicity understood in the research could contribute to the formative process of teaching and learning, it resulted in the construction of a product, that is, a memory game composed of 34 cards which are composed of the scientific name and popular name of medicinal plants as well like the image of each plant. The game aims to be applied in schools as an incentive to knowledge and appreciation of popular wisdom. Finally, the research was combined with the commitment to preserving the history of a people as a construction of a social and local identity.